Comparative patterns in the acquisition of English negation by speakers of French Creole and Creole English - Simmons-McDonald, Hazel
This article describes a resource packet that utilizes a four-point approach to make environmental action concerning land use more accessible to teachers. The points are: 1) construct a map of the area under consideration; 2) assess the impact of historical development, natural cycles, mining, and eco-tourism on the problem; 3) research land use options; and 4) encourage conservation
DOI: 10.1111/j.1467-1770.1994.tb01448.x
Keywords: French lexicon Creole